проверьте правильность решения 3 \times \sqrt[10]{ {x}^{2} - 3} + \sqrt[5]{ {x}^{2} - 3} = 4
(одз)
Замена на y : x^2-3
D=9+4*1*4=25
y1=-4(не подходит); y2=1
ответ x=2?


{x}^{2} - 3 \geqslant 0 \\ {x}^{2} \geqslant \sqrt{3}
3y + {y}^{2} = 4
{y}^{2} + 3y - 4 = 0
\sqrt[10]{ {x}^{2} - 3} = 1 \\ {x}^{2} - 3 = 1 \\ x = 2

tomakor tomakor    2   05.06.2020 22:02    0

Ответы
gshsjtzjts gshsjtzjts  15.10.2020 13:13

x₁=2 x₂=-2

Объяснение:

Упущен второй корень -2

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра